Integrating QR Code Technology in Elementary Science Content: A Developmental Study on Critical Thinking Skills - Ibrahim; Nurwahidah; Ni Made Yeni Suranti; Nurkhaerat Alimuddin (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills among prospective elementary school teachers remain limited, requiring innovative approaches in learning. This study developed and evaluated QR Code–based teaching materials for the course Basic Concepts of Elementary School Science to enhance students’ critical thinking. Using a quasi-experimental one-group pretest–posttest design with 59 PGSD students, critical thinking was assessed through four dimensions: clarification, assessment, inference, and strategy. Results showed a significant improvement, with an average N-Gain of 0.429 (moderate), indicating meaningful progress in students’ critical thinking abilities. Score distributions shifted markedly toward higher categories, with the most consistent improvement in the strategy dimension. These findings demonstrate that QR Code–based materials not only make learning more flexible and interactive but also effectively foster higher-order thinking skills. The study concludes that integrating such materials into teacher education curricula is essential to strengthen 21st-century competencies and better prepare future elementary school teachers.